Conceptual Model to use Citizen Science as a tool to generate public policies for Preservation and Conservation of ecosystems - Silva, Sidnei Pereira da; Hanai, Frederico Yuri (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – This study proposes a conceptual model for implementing Citizen Science as a tool for ecosystem conservation and preservation, focusing on the active engagement of communities in public policy formulation.Methodology – The research employed a systematic literature review and case study analysis to outline existing ideas and possibilities. The Vosviewer software was used to systematize keywords and guide the model's construction.Originality/relevance – The study addresses the theoretical gap related to the limited development of Citizen Science projects in Brazil, which predominantly follow an observer-based approach, resulting in awareness but limited political engagement.Results – The findings indicate that regionalizing the application of Citizen Science can foster local community involvement in problem-solving, generating relevant scientific data and insights for public policies aimed at biodiversity conservation.Theoretical/methodological contributions – The proposed regionalization and use of Citizen Science expand theoretical and methodological approaches in the field, connecting science, communities, and public policies.Social and environmental contributions – The model suggests pathways for community engagement in conservation and preservation actions, with potential impacts on public policy development and biodiversity strengthening.
Keywords: Citizen Science; Conceptual Model; Ecosystems; Public Policies